Csk controls leukocyte extravasation via local regulation of Src family kinases and cortactin signaling - Stegmeyer, Rebekka I.; Holstein, Katrin; Spring, Kathleen; Timmerman, Ilse; Xia, Min; Stasch, Malte; Möller, Tanja; Nottebaum, Astrid F.; Vestweber, Dietmar (Frontiers in Immunology, 2024)
C-terminal Src kinase (Csk) targets Src family kinases (SFKs) and thereby inactivates them. We have previously shown that Csk binds to phosphorylated tyrosine 685 of VE-cadherin, an adhesion molecule of major importance for the regulation of endothelial junctions. This tyrosine residue is an SFK target, and its mutation (VE-cadherin-Y685F) inhibits the induction of vascular permeability in various inflammation models. Nevertheless, surprisingly, it increases leukocyte extravasation. Here, we investigated whether endothelial Csk is involved in these effects. We found that the deficiency of Csk in endothelial cells augments SFK activation and the phosphorylation of VE-cadherin-Y685 but had no net effect on vascular leak formation. In contrast, the lack of endothelial Csk enhanced leukocyte adhesion and transmigration in vitro and in vivo. Furthermore, the silencing of Csk increased tyrosine phosphorylation of the SFK substrate cortactin. Importantly, the effects of Csk silencing on the increase in SFK activation, cortactin phosphorylation, and neutrophil diapedesis were all dependent on Y685 of VE-cadherin. Deletion of cortactin, in turn, erased the supporting effect of Csk silencing on leukocyte transmigration. We have previously shown that leukocyte transmigration is regulated by endothelial cortactin in an ICAM-1-dependent manner. In line with this, blocking of ICAM-1 erased the supporting effect of Csk silencing on leukocyte transmigration. Collectively, our results establish a negative feedback loop that depends on the phosphorylation of VE-cadherin-Y685, which recruits Csk, which in turn dampens the activation of SFK and cortactin and thereby the clustering of ICAM-1 and the extravasation of neutrophils.